2023
DOI: 10.1128/mbio.00243-23
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin Binding Protein Substitutions Cooccur with Fluoroquinolone Resistance in Epidemic Lineages of Multidrug-Resistant Clostridioides difficile

Abstract: Fluoroquinolone and cephalosporin use in healthcare settings has triggered outbreaks of high-mortality, multidrug-resistant C. difficile infection. Here, we identify a mechanism associated with raised cephalosporin MICs in C. difficile comprising amino acid substitutions in two cell wall transpeptidase enzymes (penicillin binding proteins).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 102 publications
1
4
0
Order By: Relevance
“…However, this hypothesis is not supported by our data as 4→3 PG cross-links were more abundant in antibiotic-treated cells. In line with this result, biochemical analyses of the purified class A PBP PBP1 and the class B PBP PBP2 of C. difficile, which are respectively essential for cross-links synthesis during vegetative cell division and elongation, revealed that both enzymes are insensitive to most cephalosporins and carbapenems 32,33 The only other S2. See also Table S2 for the structure of all identified muropeptides.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, this hypothesis is not supported by our data as 4→3 PG cross-links were more abundant in antibiotic-treated cells. In line with this result, biochemical analyses of the purified class A PBP PBP1 and the class B PBP PBP2 of C. difficile, which are respectively essential for cross-links synthesis during vegetative cell division and elongation, revealed that both enzymes are insensitive to most cephalosporins and carbapenems 32,33 The only other S2. See also Table S2 for the structure of all identified muropeptides.…”
Section: Discussionsupporting
confidence: 55%
“…However, this hypothesis is not supported by our data as 4→3 PG cross-links were more abundant in antibiotic-treated cells. In line with this result, biochemical analyses of the purified class A PBP PBP1 and the class B PBP PBP2 of C. difficile , which are respectively essential for cross-links synthesis during vegetative cell division and elongation, revealed that both enzymes are insensitive to most cephalosporins and carbapenems 32,33 The only other explanation to the observed structural changes is the inhibition of at least one D,D-carboxypeptidase. Activation of the L,D-transpeptidation pathway leading to β-lactam resistance in E. faecium and E. coli requires the production of a β-lactam-insensitive D,D-carboxypeptidase to generate the tetrapeptide substrate of LDTs 11,31 .…”
Section: Discussionmentioning
confidence: 54%
“… 14 The emergence of epidemic C. difficile RT027 in the early 2000s was notably associated with resistance to fluoroquinolones and, more recently, high-level resistance to cephalosporins has been also associated with this outbreak. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms by which MreE mutations increase resistance to specific classes of beta-lactam antibiotics [7] [8,9] are as yet undefined and may include reduced binding affinity of affected antibiotic classes, in addition to interaction with other genomic loci that can produce higher levels of resistance, a finding suggested by the fact that transfer of the mreE alleles alone into susceptible strains did not elevate most cephalosporin MICs to the level of the original parent strain (Fig 2C). The gene-level variants also provide targets to aid in the detection of cephalosporin resistance, whether by strain genomic analyses or with targeted mreE probes to evaluate primary patient samples for resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…Variants in the pathogen's penicillin-binding protein 2 (PBP2) have also been identified that have reduced binding-affinity to certain beta-lactam classes, including cephalosporins and carbapenems [7]. However, causative effects of these variants on phenotypic resistance in vitro and in vivo have not yet been defined, limiting our understanding of their role in patient disease [8][9][10].…”
Section: Introductionmentioning
confidence: 99%